Linguistic Landscape and Cultural Identity of Sanjai Shop Signs in Bukittinggi - Elvonny, Tia Kharina; Febriansyah, Gema; Chairina, Melyanda Agustin (Linguistik : Jurnal Bahasa dan Sastra, 2025)
Linguistic landscape refers to the visibility of languages in public spaces through written signs that reflect both communication and identity. This study examines the linguistic landscape and cultural identity of Sanjai shop signs in Bukittinggi and its surrounding areas, including Agam Regency. Using a descriptive qualitative method, data were collected through direct observation, documentation using photographs, and interviews with shop owners. The study focuses on the languages and symbols appearing on the shop signs and their meanings. The results show that Sanjai shop signs feature monolingual, bilingual, and multilingual expressions. The monolingual signs use Minangnese, Indonesian, or Bataknese, while the bilingual signs combine Minangnese and Indonesian. Bilingual signs serve to convey both local identity and product appeal to a wider audience. The use of Bataknese in border areas illustrates language adaptation along major trade routes like the Trans-Sumatra Highway. Non-linguistic signs such as Rumah Gadang motifs, Jam Gadang images, Sianok Canyon pictures, and Marawa colors strengthen the cultural identity of Minangkabau. The study concludes that Sanjai shop signs are not only commercial tools but also media for preserving and promoting Minangkabau cultural identity through both linguistic and visual elements.